Inhibition of Zinc Corrosion in H2SO4 by Hexamethylenetetramine - Abdul Jameel, A.; Elangovan, P.; Balakrishnan, K. (Asian Journal of Chemistry, 2010)
The inhibition of corrosion of zinc in H2SO4 by hexamethylenetetramine, thiourea and propargyl alcohol has been studied by potentiodynamic polarization method. The study shows that the inhibitor efficiency increases with temperature for hexamethylenetetramine but it is a less effective corrosion inhibitor. The amount of inhibitor of zinc dissolution is found to be dependent on the concentration of the inhibitor. The corrosion current increases with increase in thiourea and propargyl alcohol concentrations indicating that they accelerate the zinc dissolution reaction in H2SO4 .